FGF1 Signaling Modulates Biliary Injury and Liver Fibrosis in the Mdr2−/− Mouse Model of Primary Sclerosing Cholangitis - April O’Brien; Tianhao Zhou; Tori White; Abigail Medford; Lixian Chen; Konstantina Kyritsi; Nan Wu; Jonathan Childs; Danaleigh Stiles; Ludovica Ceci; Sanjukta Chakraborty; Burcin Ekser; et al. (Hepatology Communications, 2022)
Fibroblast growth factor 1 (FGF1) belongs to a family of growth factors involved in cellular growth and division. MicroRNA 16 (miR‐16) is a regulator of gene expression, which is dysregulated during liver injury and insult. However, the role of FGF1 in the progression of biliary proliferation, senescence, fibrosis, inflammation, angiogenesis, and its potential interaction with miR‐16, are unknown. In vivo studies were performed in male bile duct–ligated (BDL, 12‐week‐old) mice, multidrug resistance 2 knockout (Mdr2−/−) mice (10‐week‐old), and their corresponding controls, treated with recombinant human FGF1 (rhFGF1), fibroblast growth factor receptor (FGFR) antagonist (AZD4547), or anti‐FGF1 monoclonal antibody (mAb). In vitro, the human cholangiocyte cell line (H69) and human hepatic stellate cells (HSCs) were used to determine the expression of proliferation, fibrosis, angiogenesis, and inflammatory genes following rhFGF1 treatment. PSC patient and control livers were used to evaluate FGF1 and miR‐16 expression. Intrahepatic bile duct mass (IBDM), along with hepatic fibrosis and inflammation, increased in BDL mice treated with rhFGF1, with a corresponding decrease in miR‐16, while treatment with AZD4547 or anti‐FGF1 mAb decreased hepatic fibrosis, IBDM, and inflammation in BDL and Mdr2−/− mice. In vitro, H69 and HSCs treated with rhFGF1 had increased expression of proliferation, fibrosis, and inflammatory markers. PSC samples also showed increased FGF1 and FGFRs with corresponding decreases in miR‐16 compared with healthy controls. Conclusion: Our study demonstrates that suppression of FGF1 and miR‐16 signaling decreases the presence of hepatic fibrosis, biliary proliferation, inflammation, senescence, and angiogenesis. Targeting the FGF1 and miR‐16 axis may provide therapeutic options in treating cholangiopathies such as PSC.